Lexical-Semantic Characteristics of Expressions Made Through Parts of the Human Body (in the example of French and Uzbek languages) - Salimovna , Hojiyeva Gulchehra; Anvar qizi , Olimova Madina (Excellencia: International Multi-disciplinary Journal of Education (2994-9521), 2025)
In this article, the role of phraseological units in linguistics, in particular, the unique lexical-semantic and comparative features in the formation of phraseology formed by means of human body parts, is analyzed on the example of two unrelated languages: French and Uzbek.